Dirac Particles Emission from An Elliptical Black Hole - Yuant Tiandho (Indonesian Journal of Science and Technology, 2017)
According to the general theory of relativiy, a black hole is defined as a region of spacetime with super-strong gravitational effects and there is nothing can escape from it. So in the classical theory of relativity, it is safe to say that black hole is a "dead" thermodynamical object. However, by using quantum mechanics theory, Hawking has shown that a black hole may emit particles. In this paper, calculation of temperature of an elliptical black hole when emitting the Dirac particles was presented. By using the complexpath method, radiation can be described as emission process in the tunneling pictures. According to relationship between probability of outgoing particle with the spectrum of black body radiation for fermion particles, temperature of the elliptical black hole can be obtained and it depend on the azimuthal angle. This result also showed that condition on the surface of elliptical black hole is not in thermal equilibrium.